Analysis of Factors Associated With Recurrence of Early-Stage Endometrial Carcinoma and Atypical Endometrial Hyperplasia in Infertile Women After In Vitro Fertilization Treatment - Guo, Yaxing; Zong, Xuan; Li, Hongzhen; Qiao, Jie (Frontiers in Oncology, 2022)
Purpose To explore the relationship between different artificial reproductive treatment (ART) strategies and tumor outcomes, by analyzing clinical data of patients with endometrial carcinoma (EC) and atypical endometrial hyperplasia (AEH). Methods This retrospective study was performed in a tertiary hospital. Patients (n=131) with EC or AEH, who underwent in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment between June 2010 and June 2021, were divided into a recurrence group and a non-recurrence group. Clinical characteristics and tumor outcomes were assessed. Results 131 patients were followed up for 4-132 months; 33 patients had recurrence, the recurrence rate was 25.2%, 3-year recurrence-free survival (RFS) rate was 83.2 ± 3.4%, and the 5-year RFS rate was 72.9 ± 4.4%. Factors including the frequency of controlled ovarian stimulation (COS) and the total days of ovarian stimulation had no significant effect on the recurrence of tumor lesions (p=0.368 and 0.969, respectively). Histology type (HR: 4.94, 95%CI: 2.41-10.15, p <0.001) and successful/un successful live birth (HR: 0.30, 95%CI: 0.14-0.65, p=0.003) were independent factors of recurrence. Twenty-two of the 82 patients who received a single COS had recurrence. Different COS protocols, the total dose of gonadotropin (Gn), and the serum E2 level on the trigger day had no significant effect on recurrence (p=0.326, 0.889 and 0.468, respectively). Conclusions The degree at which an endometrial lesion progresses into carcinoma is a key factor affecting the recurrence of EC/AEH in patients after IVF/ICSI treatment, and successful live birth is a protective factor for the recurrence of endometrial lesions. Different COS protocols and COS frequencies, as well as the dosage and duration of Gn used during IVF did not affect the recurrence of endometrial lesions.